Effects of 1‐week sacral nerve stimulation on the rectal intestinal epithelial barrier and neuromuscular transmission in a porcine model. Issue 1 (11th November 2014) - Provost, M.; Brégeon, J.; Aubert, P.; Duchalais‐Dassonneville, E.; D'Aldebert, E.; Vergnolle, N.; Neunlist, M.; Meurette, G.
Abstract Background Sacral nerve stimulation (SNS) is a validated treatment for fecal incontinence, although the mechanism of action remains unknown. Short‐term effects of SNS on the intestinal epithelial barrier (IEB) have been reported previously. The aim of our study was to assess the impact of a 1‐week SNS on the IEB in a preclinical model. Methods Fourteen pigs were implanted for bilateral SNS. Seven pigs received 7‐day stimulation, whereas the remaining animals received no stimulation. Rectal biopsies were performed before and after SNS. We assessed IEB permeability, mucosal tight junction and cytokine mRNA expression, IL‐6 production in an organotypic culture model, and neuromuscular transmission in muscle strips. Key Results IEB permeability was not modified after stimulation, as compared with baseline. The PAR‐induced increase in IEB permeability and the mucosal ZO‐1 mRNA decrease observed in the controls were not observed into the stimulated group. Cytokine overexpression was not observed in the mucosa in either group. SNS decreased IL‐6 production in the organotypic culture model. In the stimulated group, the area‐under‐the‐curve of the EFS‐induced contractile response was significantly increased. Conclusions & Inferences The main conclusions of our work are (i) the successful development of a preclinical model of bilateral SNS and (ii) in physiological conditions, 1‐week SNS did not lead to functional changes in the mucosa. While under stress‐induced conditions, SNS modified the properties of the IEB, leading to a decrease in its permeability. Neuromuscular transmission was modified by SNS, leading to neuronal hyperexcitability. These results add evidence to the reinforcement of the IEB by SNS.